La piratería de las obras musicales y su incidencia en los derechos de autor del músico ecuatoriano: propuesta de reforma al art. 208-a del código orgánico integral penal - Sáenz Manosalvas, Ruth Genoveva (2017)
This research aims to show the rapid advance of music piracy on the market and how has this affected musicians and Ecuadorian composers, establish a solution from a legal point of view, to eradicate this type of behavior ranging at the expense of copyright. Piracy is an illegal activity that generate both fiscal damage such as unfair competition to the domestic industry and the formal commercial activities. In addition, they have created a climate of lawlessness, spoiled by the population, which, by buying smuggled goods and "pirates" supports it. The developing country, which is part of Ecuador, have the distinction of having inefficient judicial systems, so that there may be an ultra-modern legal framework, but no; this uniqueness allows, in certain types of discretionary acts, the people determine what is right and what is not. This leads to a process of legitimizing actions that each individual performs before opting for a particular behavior. Smuggling is due in large part to the existence of a commercially attractive margin on these activities, combined with the perception of low risk by the state's inability to exercise adequate control in the border areas and generally in the country, this is compounded by the existence of sectors of the population found in this activity their only source of income, since the situation in which the country finds itself is increasingly critical about the lack of formal employment, well paid, and with adequate social protection is the main problem facing women and Ecuadorian men. The development of this research in the literature review contains the following topics: Conceptual Framework concepts of Intellectual Property, Copyright, Moral Law, Estate Law, Intellectual Piracy; Marco Doctrinal Historical Overview Intellectual Property Copyright Legal Nature of Copyright, Theory of Copyright as a Real Law or Property Rights Theory of the well-known personality as personal rights, Rights Theory intellectuals Object of Copyright, Moral Rights and Property, Right to Play, Public Communication, Distribution law, law Import. Copyright adaptation, translation or transformation of creation: Legal Framework, the Constitution of the Republic of Ecuador, Intellectual Property Law, the penalties in the Ecuadorian Criminal Code, International Treaties; and Comparative Law: of Colombia, Peru and Bolivia, Subsequently the methods and techniques that helped me testing the hypothesis are specified. Field research with interviews and surveys with which it has been proved the existence of the infringement of the copyright, checking the general and specific objectives, then the discussion hypothesis testing, legal, doctrinal foundations and opinion that supports the proposed reform. Then end with conclusions, recommendations, then I present the proposed reform.